Math, asked by joevansimoes, 1 year ago

SinA/1-CosA + TanA/1+CosA=Cos²A+1/SinA×CosA

Answers

Answered by Anonymous
12

Correct Question :-

Prove that : sinA/(1 - cosA) + tanA/(1 + cosA) = (cos²A + 1)/sinA * cos A

Solution :-

 \sf \dfrac{sinA}{1 - cosA} +  \dfrac{tanA}{1 + cosA} =  \dfrac{cos^{2} A + 1}{sinA \times cosA}

Consider RHS

 \sf  = \dfrac{sinA}{1 - cosA} +  \dfrac{tanA}{1 + cosA}

Taking LCM

 \sf  = \dfrac{sinA(1 + cosA) + tanA(1 - cosA}{(1  -  cosA)(1 + cosA)}

 \sf  = \dfrac{sinA+ sinA.cosA + tanA - tan A.cosA}{ {1}^{2}   -  cos ^{2} A}

[ Because (x - y)(x + y) = x² - y² ]

 \sf  = \dfrac{sinA+ sinA.cosA + tanA -  \dfrac{sinA}{cosA} .cosA}{1   -  cos ^{2} A}

[ Because tanA = sinA/cosA ]

 \sf  = \dfrac{sinA+ sinA.cosA + tanA -  sinA}{sin^{2} A}

 \sf  = \dfrac{sinA.cosA + tanA}{sin^{2} A}

 \sf  = \dfrac{sinA.cosA +  \dfrac{sinA}{cosA} }{sin^{2} A}

Taking sinA common in numerator

 \sf  = \dfrac{sinA \bigg(cosA +  \dfrac{1}{cosA}  \bigg)}{sin^{2} A}

 \sf  = \dfrac{ cosA +  \dfrac{1}{cosA}}{sin A}

Taking LCM in numerator

 \sf  = \dfrac{ \dfrac{cos^{2} A +1 }{cosA}}{sin A}

 \sf  = \dfrac{cos^{2} A +1 }{sinA.cosA}

Hence proved.

Similar questions